«Memoria de rituales cotidianos» o el alfajor, el burrito, el cucú y el cuarteto - Yaya Aguilar, Ana Gabriela (Universidad Nacional del Litoral, 2021)
What follows is an analysis of two electroacoustic pieces Retrato sonoro de Córdoba (1999) and Memorias de rituales cotidianos (2008) by Gonzalo Biffarella, a composer based in Córdoba. The first piece is amontage of sounds recorded in the city of Córdoba, that relate semantically to it. The secondwas composed as an elaboration of such montage, applying electroacoustic procedures, which account for a piece that can be accommodated in the repertoire without any frictions and, at the same time, attenuate those features which sound local. To think the relationship between these musical works, we proposeto critically analyze some of the ideas concerning these topics, especially in Argentina, with special attention on contemporary music in the XXIst century in our territories. Thus, from the frictions between a type of hearing focused on technical–compositional aspects and one concerned with the «semantics» of sounds, we aim to show how, in this particular piece, singular contradictions regarding the problem of identity appear.